Sensibilização de profissionais da saúde quanto aos aspectos psicossociais das pessoas com anemia falciforme - Denardi, Vanilda de Fátima de Andrade Matos (2016)
Sickle-Cell Anemia (SCA) is a hereditary, serious and incurable genetic disease, but an early diagnosis and proper treatment make a quality growth and development possible for the affected children. This study – with a qualitative, descriptive and exploratory nature – intended to raise awareness among health professionals of the psychosocial aspects of people with SCA in a public hospital in Southern Brazil. The data collection occurred through meetings with discussion groups composed by professionals of different fields in the health area. The participants of the research were two nurses, one doctor, one social worker, two nursing technicians, two nursing assistants, one teacher, and one administrative assistant. They were all between 31 and 66 years old, with a professional experience time ranging from 11 to 47 years. In order to collect the data, three meetings were performed, lasting 35 minutes each. They were based on three guiding questions: What are the meanings of the SCA? What is the care of the person with SCA like (in the eyes of the professional)? And how could the qualified care of the people with SCA be? Each meeting was based on one of the listed questions. The discussion group was composed by ten participants in the first meeting, nine in the second one, and in the third meeting there were six participants. The discussions were audio recorded, transcribed and later analyzed according to the principles of Social Constructionism, given the fact that knowledge isn’t definitive, but in constant renewal due to the interactions between people (Gergen & Gergen, 2010). As argued by Rasera and Japur (2001), knowledge is built from the interactions between people. The data analysis was performed having as base the relevant moments that indicated the production of meaning regarding the SCA, and in a way that they matched the proposals of the specific goals. The exercise provided a chain of reflections about the SCA, such as the communication flaw when approaching the parents to report the diagnosis; the fact that the personnel that constitute the health staff, as well as the school team, don’t hold the knowledge regarding the disease; the team’s potentials and insufficiencies when it comes to the responsibility and commitment to the cared-for person; and finally, taking the knowledge insufficiency of the participants into account, it’s revealed the need for capacitation in order to better manage psychosocial aspects.